2016
DOI: 10.1017/s1751731115002104
|View full text |Cite
|
Sign up to set email alerts
|

Do nurse sows and foster litters have impaired animal welfare? Results from a cross-sectional study in sow herds

Abstract: Increasing litter size has led to introduction of so-called nurse sows in several EU countries. A nurse sow is a sow receiving piglets after having weaned her own piglets and thereby experiencing an extended lactation. In order to analyse whether nurse sows have more welfare problems than non-nurse sows a cross-sectional study was conducted in 57 sow herds in Denmark. Clinical observations were made on nurse and non-nurse sows and their litters. The clinical observations were dichotomized and the effect of bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
0
32
1
Order By: Relevance
“…Our study indicates that nurse sows that does not show postweaning estrus or had health problems during their lactation are culled without subsequent service. A previous study also reported a high risk of nurse sows having udder wounds and bursa on joint legs (Sørensen, Rousing, Kudahl, Hansted, & Pedersen, 2016), which might be caused by the occurrence of teat fights by piglets (Schmitt, Baxter, Boyle, & O'Driscoll, 2019), and by the prolonged stay in farrowing crate. Higher culling rate and lower parity at removal in nurse sows also can explain the discrepancy between the increased WMI in nurse sows but no difference between nurse and non-nurse sows in lifetime non-productive days.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our study indicates that nurse sows that does not show postweaning estrus or had health problems during their lactation are culled without subsequent service. A previous study also reported a high risk of nurse sows having udder wounds and bursa on joint legs (Sørensen, Rousing, Kudahl, Hansted, & Pedersen, 2016), which might be caused by the occurrence of teat fights by piglets (Schmitt, Baxter, Boyle, & O'Driscoll, 2019), and by the prolonged stay in farrowing crate. Higher culling rate and lower parity at removal in nurse sows also can explain the discrepancy between the increased WMI in nurse sows but no difference between nurse and non-nurse sows in lifetime non-productive days.…”
Section: Discussionmentioning
confidence: 94%
“…The reason that only 10% of the nurse sows were repeatedly used as a nurse could be due to that approximately half of all nurse sows were parity 5 or higher sows. There are several other criteria for choosing nurse sows, such as sows having good body condition, normal or high feed intake and good nursing behavior (Bruun et al, 2016;Sørensen, Rousing, Kudahl, Hansted, & Pedersen, 2016;Schmitt, Baxter, Boyle, & O'Driscoll, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A low body condition score increases the risk of shoulder wounds ( 22 ) and impaired fertility ( 23 ). A cross-sectional study conducted in 57 sow herds in Denmark showed that nurse sows had significantly higher prevalence of udder wounds and swollen bursa on legs compared to conventional sows ( 6 ). There were, however, no differences in body condition or prevalence of shoulder ulcers.…”
Section: Resultsmentioning
confidence: 99%
“…Older foster piglets are also more easily accepted compared to newborn by sows at weaning ( 5 ). The two-step nurse system is known to be more commonly used in Denmark where nurse sows are used to a wide extent ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though nurse sow usage may appear an attractive option, care should be given to manage the increased piglet movement and so risk of disease. The extended lactation of nurse sows could potentially result in sow welfare breaches as it will result in an increased period of confinement within a crate and little respite from older piglets [ 97 ]. No differences in physiological indicators of stress have been detected in nurse sows delivering a 40 day lactation [ 98 ], and so perhaps this is a suitable maximal lactation length.…”
Section: Disease Riskmentioning
confidence: 99%